INCREASING STUDENT CREATIVITY THROUGH A PROJECT BASED LEARNING MODEL ASSISTED BY LOCAL WISDOM ON VIBRATIONS AND WAVES MATERIAL CLASS 8 MTs - Taqwilawaty, Indah; Azizahwati, Azizahwati; Sahal, Muhammad (Universitas Lambung Mangkurat, 2024)
This study aims to determine the increase in creativity ability of grade 8 students of Madrasah Tsanawiyah (MTs) after being given learning using a project-based learning (PjBL) model assisted by local wisdom. The research conducted was pre-experiment with a one-shot case study design. This research was carried out at MTs with class VIII research subjects totaling 31 students. Data collection techniques use observation sheets of student creativity. The data analysis carried out is descriptive quantitative. The results showed that there was an increase in creativity after being given the application of the Project Based Learning model assisted by local wisdom in grade VIII.1 students. This is evidenced by the results of the observation sheet that the creativity of students at each meeting has increased, namely in the first meeting the observation results were 58% in the creative enough category, the observation results of the second meeting 78% in the creative category, the observation results of the third meeting 88% in the very creative category and the observation results of the fourth meeting 97% in the very creative category. From the data obtained, it can be seen that at each meeting, the level of creativity of grade 8 MTs students always increases after using a project-based learning model assisted by local wisdom, especially on vibration and wave materials. The project-based learning model can also be used in other more interesting lessons to obtain better results.